2021
DOI: 10.1186/s13045-021-01178-z
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cells targeting CD99 as an approach to eradicate T-cell acute lymphoblastic leukemia without normal blood cells toxicity

Abstract: CAR T cell therapy has shown dramatic clinical success in relapsed or refractory B-ALL and other hematological malignancies. However, the loss of specific antigens, cell fratricide, T cell aplasia, and normal T cell separation are challenges in treating T cell leukemia/lymphoma with CAR T therapy. CD99 is a promising antigen to target T-ALL and AML as it is strongly expressed on the majority of T-ALL and AML. Here, we isolated a low-affinity CD99 (12E7) antibody, which specifically recognizes leukemia cells ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…In particular, solid tumor types such as lung cancer (80), breast cancer (84) and gastric cancer (85) associated with vascular, mesenchymal and inflammatory architecture can be better recapitulated in vivo with PDX-based xenograft models. These preclinical models reflecting tumor heterogeneity are key for obtaining an understanding of how this heterogeneity affects responses to CAR-T cell immunotherapy and how it may change during treatment both at the genomic and at the phenotypic levels (86)(87)(88)(89)(90).…”
Section: Preclinical Models For Testing Car-t Cells and Off-the-shelf...mentioning
confidence: 99%
“…In particular, solid tumor types such as lung cancer (80), breast cancer (84) and gastric cancer (85) associated with vascular, mesenchymal and inflammatory architecture can be better recapitulated in vivo with PDX-based xenograft models. These preclinical models reflecting tumor heterogeneity are key for obtaining an understanding of how this heterogeneity affects responses to CAR-T cell immunotherapy and how it may change during treatment both at the genomic and at the phenotypic levels (86)(87)(88)(89)(90).…”
Section: Preclinical Models For Testing Car-t Cells and Off-the-shelf...mentioning
confidence: 99%
“…Importantly, it could retain a majority of normal T cells in vivo (35). CD99 is highly expressed in newly diagnosed T-ALL patients, and it represents a novel target for T-ALL (36). Furthermore, chemokine receptor CCR9 is expressed in over 70% of T-ALL patients, and only on less than 5% of normal T cells.…”
Section: Targets For Car-t Cell Therapy In T Cell Lymphoblastic Leuke...mentioning
confidence: 99%
“…Identifying tumor-specific antigens that restrict T-cell expression is another strategy to avert fratricide and overcome CAR T therapy for T-ALL ( Figure 3 B). Currently, TRBC1/2, CDR3, CD1a, CD4, CCR7, CCR9, CD33, CD30, and CD99 are now being identified and evaluated as targets for CAR T therapy to treat T-cell malignancies ( Figure 3 B, Table 1 ) [ 46 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. These biomarkers have limited expression on normal T cells and antigen-derived CAR T cells continue to proliferate normally.…”
Section: Fratricide and Promising Strategiesmentioning
confidence: 99%
“…Furthermore, our group also tried to identify tumor-specific antigens for T-ALL CAR T therapy and demonstrated that CD30 and CD99 are potential options for R/R T-ALL cases [ 59 , 72 ]. In detail, CD99 is expressed at very high levels in newly diagnosed T-ALL patients and at low levels in normal hematopoietic cells.…”
Section: Fratricide and Promising Strategiesmentioning
confidence: 99%